Effects of phosphorus slag powder and polyester fiber on performance characteristics of asphalt binders and resultant mixtures. (15th June 2017) - Sheng, Yanping; Zhang, Ben; Yan, Yu; Chen, Huaxin; Xiong, Rui; Geng, Jiuguang
Highlights: PSP increased the binder viscosity resulting in enhanced mixture rutting resistance. PF improved the mixture resistance to low-temperature cracking and moisture damage. PSP and PF can be properly recycled together for satisfactory mixture performance. Abstract: The objective of this study was to investigate the effect of phosphorus slag powder (PSP) and polyester fiber (PF) on the rheological properties of asphalt binder and performance characteristics of resultant mixtures. It is also of great interest to determine whether the PSP can be used to replace conventional filler (i.e., limestone powder) without negatively affecting the mixture performance. A laboratory experiment was developed which included characterization of PSP and PF, determinations of the optimum content of PF and optimum PSP-binder ratio, and performance evaluation of asphalt mixtures with various combinations of PF, PSP and limestone powder. The PSP behaved effectively as a mineral filler such that it increased the binder viscosity resulting in enhanced mixture rutting resistance. The use of PF significantly improved the mixture resistance to low-temperature cracking and moisture damage as indicated by the flexural strain and tensile strength ratio results. Overall, mixture with 3% PF at the PSP-binder ratio of 1.0 outperformed the others with limestone powder and/or PF, indicating the feasibility of recycling PSP and PF into asphalt mixtures for satisfactory mixture performance.